Factors affecting females’ participation in leadership positions in RMG industry, Bangladesh - Islam, Md Asadul; Jantan, Amer Hamzah; Saimoon, Ayesha (International Journal of Scientific and Research Publications, 2017)
This paper aims to examine the use of succession planning, flexibility and communication to ensure female participation in the leadership positions in the Ready Made Garments (RMG) industry of Bangladesh. Study used quantitative strategy and cross-sectional survey method to collect the data from 250 employees with education level of intermediate to masters. Results demonstrated that more than 90% of participants rated the level of succession planning, flexibility and communication used in RMG organisations as low to bring females into leadership positions. Since, no study identifying the use of three antecedents in Bangladesh has been conducted so far, significance of this study lies in highlighting the exact antecedents to be improved in RMG organizations of Bangladesh to increase female participation in leadership positions.